Black African cinema - Ukadike, Nwachukwu Frank (University of California Press, 1994)
From the proselytizing lantern slides of early Christian missionaries to contemporary films that look at Africa through an African lens, N. Frank Ukadike explores the development of black African cinema. He examines the impact of culture and history, and of technology and co-production, on filmmaking throughout Africa.